Handbook of Dietary Phytochemicals 2020
DOI: 10.1007/978-981-13-1745-3_17-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Monoterpenoids

Abstract: A great number of foods, vegetables, fruits, and beverages contain various types of monoterpenoids and their related compounds. This chapter summarizes the distribution of monoterpenoids in dietary foods, vegetables, fruits, beverages, and processed foods, and their biological activity, effects, and application to our health, as well as metabolic pathways of several monoterpenoids in mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the present study, GC-MS analysis revealed the presence of monoterpenoids p -menth-1-en-9-ol and 1,8 -cineole as the dominant compounds in the hydrosol ( Table 1 ). Oxygenated monoterpenes have been previously described as compounds with anticancer activity [ 59 ]. Moteki et al [ 60 ] reported the cytotoxic activity of 1,8 -cineole in leukemia cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, GC-MS analysis revealed the presence of monoterpenoids p -menth-1-en-9-ol and 1,8 -cineole as the dominant compounds in the hydrosol ( Table 1 ). Oxygenated monoterpenes have been previously described as compounds with anticancer activity [ 59 ]. Moteki et al [ 60 ] reported the cytotoxic activity of 1,8 -cineole in leukemia cancer cells.…”
Section: Resultsmentioning
confidence: 99%